2004
DOI: 10.1152/japplphysiol.00076.2004
|View full text |Cite
|
Sign up to set email alerts
|

Neural control of muscle blood flow during exercise

Abstract: .-Activation of skeletal muscle fibers by somatic nerves results in vasodilation and functional hyperemia. Sympathetic nerve activity is integral to vasoconstriction and the maintenance of arterial blood pressure. Thus the interaction between somatic and sympathetic neuroeffector pathways underlies blood flow control to skeletal muscle during exercise. Muscle blood flow increases in proportion to the intensity of activity despite concomitant increases in sympathetic neural discharge to the active muscles, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
175
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(180 citation statements)
references
References 94 publications
4
175
0
1
Order By: Relevance
“…Late vasodilatation is mostly mediated by accumulation of local vasoactive compounds, which act directly on the vessel wall and indirectly to block sympathetic activation (functional sympatholysis). Indeed several investigators have confirmed that sympathetic vasomotor innervation is activated during exercise (52,(54)(55)(56). Despite the similar local vasodilatation occurring in both groups, relative flow at high exercise load was significantly higher in trained SHR than in trained WKY ( Figure 5), suggesting the involvement of other factor(s).…”
Section: Effects Of Training On Blood Flowmentioning
confidence: 71%
See 1 more Smart Citation
“…Late vasodilatation is mostly mediated by accumulation of local vasoactive compounds, which act directly on the vessel wall and indirectly to block sympathetic activation (functional sympatholysis). Indeed several investigators have confirmed that sympathetic vasomotor innervation is activated during exercise (52,(54)(55)(56). Despite the similar local vasodilatation occurring in both groups, relative flow at high exercise load was significantly higher in trained SHR than in trained WKY ( Figure 5), suggesting the involvement of other factor(s).…”
Section: Effects Of Training On Blood Flowmentioning
confidence: 71%
“…The mechanisms controlling blood flow during exercise are still controversial. Removal of a sympathetic vasoconstrictor (responsible for maintaining resting vascular tone) (54), accumulation of local metabolic vasodilators such as adenosine, nitric oxide, osmolarity, high CO 2 , low O 2 and pH (52,54) and high activity of the muscle pump (55) are proposed mechanisms.…”
Section: Effects Of Training On Blood Flowmentioning
confidence: 99%
“…Autonomic control of vasomotor functions could be involved in muscle metabolism (Grant, 1966;Baez, 1973;Fleming et al, 1987Fleming et al, , 1989Franken et al, 1996;Berg et al, 1997;Kurjiaka, 2004). In fact, during skeletal muscle contraction it is possible to observe a local functional vasodilation, rapidly followed by a sympathetic vasoconstriction (Thomas and Segal, 2004). Initially the rhythmic skeletal muscle contractions augment capillary perfusion (Sweeney and Sarelius, 1989) and promote the extraction of oxygen and nutrients from the blood (functional vasodilation) (Gorczynski et al, 1978;Marshall and Tandon, 1984;Van Teeffelen and Segal, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic control of vasomotor functions could be involved in the muscles metabolism (Grant, 1966;Baez, 1973;Fleming et al, 1987Fleming et al, , 1989Franken et al, 1996;Berg et al, 1997;Kurjiaka, 2004). In fact, during the contraction of a muscle it is possible to observe a local functional vasodilatation, quickly followed by a sympathetic vasoconstriction (Thomas and Segal, 2004). Initially, the contraction of muscle augment capillary perfusion (Sweeney and Sarelius, 1989) promote the extraction of oxygen and nutrients from the blood (functional vasodilation) (Gorczynski et al, 1978;Marshal and Tandon, 1984;Van Teeffelen and Segal, 2003).…”
Section: Vacht-immunoreactivitymentioning
confidence: 99%